(untitled) (Advances in Systems Science and Applications, 2018)
Various concepts of tokamaks as leaders in solving the controlled thermonuclear fusion problem are presented. The evolution of tokamaks from round in vertical cross-section tokamaks with a large aspect ratio up to tokamaks with a small aspect ratio including spherical ones is characterized. The classification of modern tokamaks according to their poloidal systems with the location of the poloidal field coils inside and outside of the toroidal field coil is given, taking into account the presence of coils inside a vacuum vessel to stabilize the plasma position. The methods of plasma diagnostics by magnetic measurements outside the plasma, actuators for both plasma magnetic and kinetic control, associated with plasma additional heating, plasma magnetic and kinetic models, instabilities and disruptions of a plasma discharge are described.